1992
DOI: 10.1227/00006123-199211000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Removal of Petroclival Meningiomas

Abstract: This is a report of 33 consecutive cases of petroclival meningioma treated surgically at our institution over the last 10 years; there were 21 women and 12 men between the ages of 27 and 68 (mean age, 52). All patients were assessed by computed tomographic scans including coronal sections and bone algorithm studies; in most cases, digital subtraction angiography and magnetic resonance imaging were also done. The largest tumor diameter was between 2 and 3.5 cm in 14 cases, 3.5 to 6 cm in 15 cases, and over 6 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(72 citation statements)
references
References 30 publications
2
68
0
2
Order By: Relevance
“…Bricolo et al and Hakuba et al showed a rate of total removal and mortality respectively of: 79% and 9%; 75% and 12%. 9,14 Our rate of total removal was 87% with a rate of mortality of 13.3%. Probably our higher success rate of total resections was related to the higher number of fatal complications and morbidity.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Bricolo et al and Hakuba et al showed a rate of total removal and mortality respectively of: 79% and 9%; 75% and 12%. 9,14 Our rate of total removal was 87% with a rate of mortality of 13.3%. Probably our higher success rate of total resections was related to the higher number of fatal complications and morbidity.…”
Section: Discussionmentioning
confidence: 77%
“…The rate of cranial nerve deficits ranged from 31% to 100%. [14][15][16][17][18][19][20] The nerve most frequently damaged during surgery and of slowest recovery is cranial nerve VI. In our series, all patients had post-operative VI nerve palsy, although the palsy was transient in 7 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complication reported is CN deficits. [1][2][3][4][5][6][7][8] In our series, although evoked potential monitoring was performed in all patients and the CN anatomy could be somewhat preserved, nine patients suffered from facial palsy, of whom six patients recovered to House-Brackmann Grade 2 after 3 months, and two patients with permanent facial palsy underwent hypoglossal-facial anastomosis with excellent results after 6 months.…”
Section: Discussionmentioning
confidence: 74%
“…In the mean follow-up of 4.3 years, no patient who underwent GTR experienced tumor recurrence (Figs. [2][3][4]. Of the 42 patients operated via the retrosigmoid approach who underwent a Simpson Grade III and IV resection, tumor regrowth was observed in three patients.…”
Section: Postoperative Coursementioning
confidence: 99%
See 1 more Smart Citation